Адміністративно-господарський статус суб'єктів інноваційної діяльності в контексті розвитку технологічних парків - Василенко, Микола Дмитрович; Василенко, Николай Дмитриевич; Vasilenko, Nikolaj (My University, 2009)
Efficiency of central authorities of executive power in innovative activity field from a d m i n i s t r a t i v e and economic law position is analysed. Central authorities of executive power is t h e subjects with economic rights and duties, although they didn't carry out economic activity directly. Such subjects are the special, because they take part in the special g o v e r n m e n t relations. Role of Ministry for Education and Science of Ukraine and S t a t e Agency for i n v e s t m e n t s and innovations of U k r a i n e as t h e central authorities of executive power at innovative s p h e r e h a s b e e n s h o w n . N e c e s s i t y to improve a m a n a g e m e n t s t r u c t u r e from t h e law positions and to devide t h e functions for c e n t r a l authorities of executive power, i n t p o d u c t i n g principle of individual responsibility.
Василенко М. Д. Адміністративно-господарський статус суб'єктів інноваційної діяльності в контексті розвитку технологічних парків / М. Д. Василенко // Наукові праці Одеської національної юридичної академії / голов. ред. С. В. Ківалов ; МОН України, ОНЮА. - Одеса : Юрид. л-ра, 2009. - Т. 8. - С. 285-295.
Keywords: адміністративно-господарський статус; господарське право; інноваційна діяльність; центральні органи виконавчої влади; технологічні парки; административно-хозяйственный статус; хозяйственное право; инновационная деятельность; центральные органы исполнительной власти; технологические парки; fdminstrative-economic s t a t u s; economic law; innovative activity; central authorities of executive power; technological parks